Carvedilol and Cardiac Biomarkers in Dialysis Patients: Secondary Analysis of a Randomized Controlled Trial - Matthew A. Roberts; Darsy Darssan; Sunil V. Badve; Robert P. Carroll; Magid A. Fahim; Brian A. Haluska; Carmel M. Hawley; Nicole M. Isbel; Mark R. Marshall; Elaine M. Pascoe; Eugenie Pedagogos; Helen L. Pilmore; et al. (Kidney & Blood Pressure Research, 2017)
Background/Aims: Cardiac biomarkers are associated with cardiac abnormalities and adverse outcomes in dialysis patients. Our aim was to report the effect of the beta-blocker carvedilol on cardiac biomarkers in adult dialysis patients. Methods: The Beta-Blocker to Lower Cardiovascular Dialysis Events Feasibility Study was a randomized controlled trial comparing carvedilol to placebo. Serum and plasma were collected before the run-in, then 6 and 12 months post-randomization to measure B-type Natriuretic Peptide (BNP), N-terminal BNP (NT-ProBNP), high-sensitivity cardiac troponins I (hs-TnI) and T (hs-TnT), and galectin-3. Left ventricular global longitudinal strain (GLS) was measured by echocardiography at baseline. Results: Seventy-two participants were recruited of whom 49 completed the run-in and were randomized to carvedilol (n=26) or placebo (n=23). Baseline echocardiography demonstrated median (inter-quartile range) GLS of -14.27% (-16.63 to -11.93). NTproBNP and hs-TnT correlated with GLS (Spearman’s rho=0.34 [p=0.018] and rho=0.28 [p=0.049], respectively). Median change scores from baseline to 12 months did not differ significantly between participants with complete biomarker data randomized to carvedilol (n=15) or placebo (n=16) for any biomarkers. Conclusions: NT-proBNP and hs-TnT were associated with GLS. However, changes in levels of the biomarkers from baseline to 12 months were not different between groups randomized to carvedilol and placebo.